Transcriptome analyses reveal photosynthesis-related genes involved in photosynthetic regulation under low temperature stress in Lavandula angustifolia Mill. - Li, Ling; Liang, Yuchen; Liu, Yinan; Sun, Zeyi; Liu, Yuning; Yuan, Zening; Fu, Chang (Frontiers in Plant Science, 2023)
In order to reveal the mechanisms of photosynthetic regulation of Lavandula angustifolia Mill. under low temperature stress, photosynthesis-related genes were screened and the molecular mechanism were analyzed for this species growing in Harbin, northeast of China. RNA-seq technique and photosynthetic physiology measurement were performed under 20℃, 10℃, and 0℃ in this study. The results showed that the observing modified rectangular hyperbola mode could accurately reflect the light-response processes under low temperature stress and the low temperature reduced the light energy utilization of L. angustifolia. The stomatal conductance decreased with the temperature dropping, which was associated with the up-regulation of LaBAM1s, LaMPK4-1 and LaMMK2. The up-regulation of LaMPK4-1 and LaMMK2 was beneficial for ROS scavenging. The improvement ofcold resistance in L. angustifolia was related to the up-regulated expression of LaFBA and LaOMTs and down-regulated expression of LaGAPAs, LaGOX, and LaTKL1s with the temperature decreasing. The up-expression of LaPSY at 10°C than it at 20°C could protect the photosynthetic organs from oxidative damage. Moreover, the photosynthetic rates at 10°C and 0°C were close to the measured values, which was related to the interactions of RCA with SBPase and Rubisco with SBPase. These findings could provide a theoretical reference for further exploring the cold tolerance mechanism of L. angustifolia, as an important aromatic plant resource, and promoting its cultivation and distribution in the northeast of China.